Continuous primary fermentation of beer with yeast immobilized on spent grains : the effect of operational conditions - Brányik, Tomáš (2004)
A one-stage continuous primary beer fermentation with immobilized brewing yeast was studied. The objective of the work was to optimize the operational conditions (aeration and temperature) in terms of volumetric productivity and organoleptic quality of green beer. The system consisted of an internal-loop airlift reactor and a carrier material prepared from spent grains (a brewing by-product). An industrial wort and yeast strain were used. The immobilized biomass (in amounts from two to sevenfold greater than free biomass) contributed 45-75% to the total fermentation. The volumetric productivity of the continuous system was as much as five times higher than that of the batch fermentation. An optimum higher-alcohols-to-esters ratio in green beer was found at approximately 2 mg/L of oxygen dissolved in wort, mixing induced by pure CO2, and temperatures at 13-16ºC. At high total biomass concentration, the diacetyl formation was low, and the volumetric productivity of the system was high. Therefore, the amount of immobilized biomass in the reactor has to be kept at high concentration by regular replacement of the carrier losses.